IMPLEMENTASI PERMAINAN BISIK BERANTAI UNTUK MENINGKATKAN MAHARAH ISTIMA’ DI ASRAMA DARUL LUGHOH AL-AROBIYYAH PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Lyien Ien, Dewi; Lathifa, Anyes (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2023)
The chain whisper game is a game played by several groups, with each group usually consisting of 4–7 people. The task of each group is to convey the sentences contained in the chained message. The aim of this research is to determine the application, inhibiting, and supporting factors of the chain whispering game to improve the listening skills of female course students at the Darul Lughoh Al Arobiyyah boarding school at the Darussalam Islamic Boarding School Blokagung Banyuwangi. So the author is interested in researching the chain whisper game because this method is still rarely used in other educational institutions. The type of research used was descriptive qualitative research taking place at the Darul Lughoh Al Arobiyyah boarding school at the Darussalam Islamic Boarding School, Blokagung Banyuwangi. Data collection was carried out using observation, interviews, and documentation methods. Meanwhile, data analysis techniques use data analysis techniques, which consist of three activity flows: data reduction, data presentation, and drawing conclusions. This research resulted in: 1) The application of the message whispering game to improve listening skills was carried out by training female students to listen to a message containing sentences or vocabulary adapted to the learning theme. The forms of children's listening activities are: female students are able to listen actively; female students are able to distinguish the intonation of words; female students are able to understand the meaning contained in the message; and female students can repeat the words they hear. 2) The inhibiting factors in implementing this game method are the lack of enthusiasm among female students, limited time, and classrooms that are still mixed with others. The supporting factors are adequate infrastructure and support from administrators. The chain whisper game is a game played by several groups, with each group usually consisting of 4–7 people. The task of each group is to convey the sentences contained in the chained message. The aim of this research is to determine the application, inhibiting, and supporting factors of the chain whispering game to improve the listening skills of female course students at the Darul Lughoh Al Arobiyyah boarding school at the Darussalam Islamic Boarding School Blokagung Banyuwangi. So the author is interested in researching the chain whisper game because this method is still rarely used in other educational institutions. The type of research used was descriptive qualitative research taking place at the Darul Lughoh Al Arobiyyah boarding school at the Darussalam Islamic Boarding School, Blokagung Banyuwangi. Data collection was carried out using observation, interviews, and documentation methods. Meanwhile, data analysis techniques use data analysis techniques, which consist of three activity flows: data reduction, data presentation, and drawing conclusions. This research resulted in: 1) The application of the message whispering game to improve listening skills was carried out by training female students to listen to a message containing sentences or vocabulary adapted to the learning theme. The forms of children's listening activities are: female students are able to listen actively; female students are able to distinguish the intonation of words; female students are able to understand the meaning contained in the message; and female students can repeat the words they hear. 2) The inhibiting factors in implementing this game method are the lack of enthusiasm among female students, limited time, and classrooms that are still mixed with others. The supporting factors are adequate infrastructure and support from administrators.